(untitled) (Current Horticulture, 2024)
The cloves of garlic (Allium sativum L.) cultivar Mukteshwar Local, after disinfection, were sprouted under in-vitro condition (85.00 % sprouting) on MS medium containing 2 mg/l GA3. The cloves were soaked in 100 ppm GA3 solution for 24 hr. Maximum number of shoot buds (7.0) was recorded in treatment containing MS + 4.0 ppm BAP + 1.0 ppm NAA. Among different treatments for shoot multiplication, treatment MS+5.0 ppm BAP+ 1.0 ppm KIN + 0.5 ppm GA3 was the best. The number of shoots also varied with the level of sugar, light intensity and, light and dark cycle on shoot multiplication. They multiplied best in 30 g/l sucrose, 5000 lux light intensity and 16:8 hr of light and dark cycle. The developed protocol may be used for mass multiplication of garlic cultivars as well as regeneration of genetically transformed cell/ tissue.